The investors' perspective on sustainable green building - Eng, Cheng Wei (2024)
The rapid global industrialization since 21st century has led to a sharp increase in climate anomalies. Traditional construction practices contribute to energy consumption, pollution, and lack of environmental consciousness within the industry. Therefore, embracing the concept of green building is crucial for mitigating environmental degradation in urban areas. This paper was to study the influence factor in investor perspective on the decision making when invest in the green building. This study seeks to identify the factors impacting potential investors and ascertain which factors have the greatest influence on investors' decisions regarding investment in green buildings in Malaysia. The study included 80 participants and found that several factors influenced investment decisions regarding green building. In this research study four factors have been anticipated, which are; subjective norms, cost/price, environmental benefits and economic benefits and were ranked among these factors to the effect on the investment decision of green building. Data will be collected using convenient sampling technique and obtained data will be analysed by using SPSS version 26 to get the value for relative important index (RII) for this research project. This study can be improved by perform on larger population in order to get the standardized data for the entire population in Malaysia. This research finding can offer insights into enhancing green development in Malaysia by providing additional data on factors influencing investor perspective toward green building investments. This data will allow us to gain a deeper understanding of the motivations and deterrents behind their investment decision in green buildings.